Theoretical solution for the impact of foundation pit excavation with support measures on the underlying shield tunnel - Kailun Ma; Tingting Liu; Xinping Li; Huirong Xu; Chuanxu Yuan; Dengxing Qu (Scientific Reports)
Abstract With the rapid development of urban rail transit construction, shield tunnels are increasingly prevalent underground in many cities, resulting in an inevitable increase in foundation pit projects located above existing shield tunnels. Close-proximity excavation of these foundation pits will inevitably alter the overlying loads on the shield tunnels, thereby inducing displacement and deformation of the tunnels themselves. To control the deformation of the underlying shield tunnels and ensure the safety of subway operations, appropriate pre-reinforcement measures must be proposed for the excavation support of foundation pits. Based on the two-stage method, this paper revises the existing Winkler foundation beam model by introducing a correction coefficient influenced by excavation time and excavation support measures to adjust the vertical additional stress calculated using Mindlin’s theory. Additionally, a foundation reinforcement influence coefficient β is introduced to modify the coefficient of subgrade reaction, and the values of β under different reinforcement modes are obtained through numerical simulation. Furthermore, based on the reconstruction project of Building A of the Free Harbor Apartment Complex in Shenzhen, the revised calculation model for vertical displacement of shield tunnels obtained in this paper is applied to a practical engineering project. By comparing the subsequent monitored displacement data with the model curves proposed in this paper, the accuracy of the revised model is verified.